Facilitating recognition of crowded faces with presaccadic attention - Wolfe, Benjamin A.; Whitney, David (Frontiers in Human Neuroscience, 2014)
In daily life, we make several saccades per second to objects we cannot normally recognize in the periphery due to visual crowding. While we are aware of the presence of these objects, we cannot identify them and may, at best, only know that an object is present at a particular location. The process of planning a saccade involves a presaccadic attentional component known to be critical for saccadic accuracy, but whether this or other presaccadic processes facilitate object identification as opposed to object detection—especially with high level natural objects like faces—is less clear. In the following experiments, we show that presaccadic information about a crowded face reduces the deleterious effect of crowding, facilitating discrimination of two emotional faces, even when the target face is never foveated. While accurate identification of crowded objects is possible, if difficult, in the absence of a saccade, accurate identification of a crowded object is considerably facilitated by presaccadic attention. Our results provide converging evidence for a selective increase in available information about high level objects, such as faces, at a presaccadic stage.